IMPROVING THE EFFICIENCY OF INVESTMENT PROJECT FINANCING IN ENERGY ENTERPRISES THROUGH INTEGRATED FINANCIAL MECHANISMS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Energy enterprises play a strategic role in ensuring economic stability, industrial growth and social welfare. The uninterrupted supply of energy resources, modernization of production and distribution networks, and introduction of energy-saving technologies directly depend on the availability of long-term investment resources. In the modern economy, the financing of investment projects in energy enterprises cannot be limited to one source of capital.